A world list of known cave-and bat guano-associated Trogidae (Coleoptera: Scarabaeoidea), and further range extension of Omorgus lindemannae (Petrovitz) - (:unkn) unknown (My University, 2025)
Trogidae are not uncommonly associated with guano deposits derived from cave-roosting bats, and less commonly with bat guano in tree hollows. Trogidae may also occur in caves without any apparent association with bat guano. Since a rather large number of reports of the foregoing behaviour is scattered through an often obscure literature, we compiled and commented on a list of Trogidae species—worldwide—that have been recorded either from caves, or from bat guano inside or outside of caves. We report on 20 named species confirmed to be cavernicolous and/or associated with bat excrement; and on an unknowable number of species hitherto identified only to genus level. Wetabulate possibly cavernicolous species for which confirmation of a cave association is required. We consider the presence in caves of half of these named species as accidental or incidental, 9 or 10 species as troglophilic, and three species as both troglophilic and bat-guanophilic. One species appears not to be a troglophile, but still a bat-guanobiont; this may be a novel life history style. No Trogidae is known to be troglomorphic or troglobitic. For three named species we present the first published evidence of a putatively cavernicolous life style. We propose that Trox perrisii Fairmaire be excluded from a compilation such as ours. We introduce our work with a critical overview of Trogidae feeding habits: they do not necessarily feed on keratinous material, as is widely assumed. We report new southern African localities that extend the range of Omorgus lindemannae (Petrovitz). Colour photos of each of the listed genera and subgenera accompany the text.
Keywords: African Research